Comparison of Corticosteroids vs Conventional Physical Therapy for Management of Adhesive Capsulitis - Ziauddin Khan, Brig. Adnan Anwar, M. Shoaib Zardad, Adnan Afsar, Awais Jameel, Tahir Nawaz (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the role of corticosteroids and conventional physical therapy for management of adhesive capsulitis Methodology: This comparative study was conducted in Orthopedic Department, Combined Military Hospital Abbottabad. March 2022 to February 2023. Patient of active adhesive capsulitis of shoulder joint diagnosed by orthopedic surgeon were recruited. Patients in group A received single shot of methylprednisolone with local anesthesia with in the joint cavity while group B received conventional physical therapy at rehab department of our hospital. Pain scores via visual analogue scale and range of motion via goniometer was compared in both groups at baseline and at 8 weeks of treatment. Results: A total of 160 patients of adhesive capsulitis were recruited. Mean age was 42.55±10.96 years. 70 (43.7%) patients were female while 90 (56.3%) were male. Baseline pain scores and range of motion parameters were not statistically significant between the two comparison groups. At the end of 8 weeks mean pain scores were statistically significantly low in patients who took intra-articular corticosteroids as compared to those who underwent physiotherapy sessions (p-value<0.001). Range of motion parameters were also statistically significantly better in patients who took corticosteroids as compared to those who underwent physiotherapy (p-value<0.001). Conclusion: Use of corticosteroids emerged as a better option for treatment of pain and restricted range of motion in patients of adhesive capsulitis when compared to routine physiotherapy offered in our clinical settings. Keywords: Adhesive Capsulitis; Corticosteroids; Efficacy; Physiotherapy